Perubahan Perseroan Terbatas Perorangan Menjadi Perseroan Terbatas Persekutuan Modal Ditinjau Dari Kemanfaatan Hukum - Br Sebayang, Ruhulina; Yenny Yuniawaty Lunandi (Universitas Ekasakti, 2024)
The government provides convenience for Micro and Small Enterprises (hereinafter abbreviated as UMK) by making a breakthrough through Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation into Law. Article 109 of Law Number 6 of 2023 concerning Job Creation reads: